2011
DOI: 10.1007/s11631-011-0526-2
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of source rocks in the Es3 and Es4 members in the Shahejie Formation of the Western Depression, Liaohe Oilfield, China

Abstract: The Western Depression of the Liaohe Basin is the major exploration area of the Liaohe Oilfield, and its main source rocks consist of the third and fourth members of the Shahejie Formation (Es 3 and Es 4 ). These source rocks are widely distributed in the depression, with semi-deep lake and fan delta as the main sedimentary facies, brown oil shale and black gray-dark gray mudstone as the main rocks, and a total thickness of 270-1450 m. The kerogens are mainly of the types I and II A , and partly of the type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Observations show that approximately 65% of hydrocarbon reservoirs are distributed in the Western Depression (Li et al, 2007;Shan et al, 2005;Teng et al, 2016;Tong et al, 2008), while hydrocarbon reservoirs in the Eastern Depression are mostly distributed along strikeslip faults. Exploration has confirmed that the main source rock of the Liaohe Subbasin is melanocratic mudstone of the 3rd member of the Shahejie Formation (Figure 4; Wang et al, 2011;Xiong et al, 2003). Source rocks in the Western Depression are mainly distributed in the Qingshui, Chenjia and Niuxintuo Sags (Shan et al, 2005;Tong et al, 2008;Figure 13a).…”
Section: Significance Of Petroleum Geologymentioning
confidence: 96%
“…Observations show that approximately 65% of hydrocarbon reservoirs are distributed in the Western Depression (Li et al, 2007;Shan et al, 2005;Teng et al, 2016;Tong et al, 2008), while hydrocarbon reservoirs in the Eastern Depression are mostly distributed along strikeslip faults. Exploration has confirmed that the main source rock of the Liaohe Subbasin is melanocratic mudstone of the 3rd member of the Shahejie Formation (Figure 4; Wang et al, 2011;Xiong et al, 2003). Source rocks in the Western Depression are mainly distributed in the Qingshui, Chenjia and Niuxintuo Sags (Shan et al, 2005;Tong et al, 2008;Figure 13a).…”
Section: Significance Of Petroleum Geologymentioning
confidence: 96%